Understanding out-of-pocket expenditure in India: a systematic review - Kamath, Sagarika; Maliyekkal, Jeffin; Elstin Anbu Raj, S.; Varshini, R. J.; Brand, Helmut; Sirur, Andria; Singh, Vishwajeet; Prabhu, Vidya; Sumit, Kumar; Kamath, Rajesh (Frontiers in Public Health, 2025)
IntroductionOut-of-pocket expenditure (OOPE) constitutes a substantial portion of healthcare costs in India, accounting for 47.1% of the Total Health Expenditure in 2019–20. Despite a decline from previous years, OOPE remains a significant financial burden, contributing to catastrophic health expenditures and impoverishment for households.MethodsA systematic review was conducted to analyze factors influencing out-of-pocket expenditures (OOPE) in India. The review adhered to predefined inclusion and exclusion criteria. Search terms were tailored to the syntax of each database to maximize retrieval, using combinations of keywords such as “out of pocket,” “India,” and “national survey.” A total of 702 citations were retrieved (PubMed: 185, Web of Science: 183, Scopus: 334), with 316 identified as duplicates. After title and abstract screening of 386 citations, 128 articles were subjected to full-text review, leading to the inclusion of 36 studies. A narrative synthesis and thematic analysis identified determinants of OOPE in the Indian healthcare context, with findings organized in tables and descriptive formats to address study heterogeneity and enhance interpretation.ResultsThis systematic and rigorous methodology ensures a comprehensive and reliable understanding of the determinants of OOPE in the Indian healthcare context. Eleven themes emerged from the review: (1) source of care and disease/ condition, (2) place of residence, (3) economic status, (4) components of OOPE, (5) age, (6) gender, (7) strategies for coping with OOPE, (8) educational attainment, (9) OOPE and institutional deliveries, (11) health insurance.DiscussionIndia’s heavy reliance on OOPE emphasizes healthcare gaps, necessitating reforms in public investment, insurance, primary care, and affordable access to ensure equity and financial protection. The lack of equitable healthcare financing instigates the challenges, leading to widespread reliance on distress financing methods.